Peptide-induced T-cell tolerance to prevent autoimmune diabetes in a transgenic mouse model. - Aichele, P (1994)
A synthetic peptide corresponding to an immunodominant epitope of lymphocytic choriomeningitis virus glycoprotein (LCMV GP) was used to prime or to tolerize CD8+ T cells in vivo, dependent on mode of immunization. Peptide-specific tolerance was then examined in transgenic mice expressing LCMV GP in the beta islet cells of the pancreas; these mice develop CD8+ T-cell-mediated diabetes within 8-14 days after LCMV infection. Specific peptide-induced tolerance prevented autoimmune destruction of beta islet cells and diabetes in this transgenic mouse model.